(untitled) (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2024)
This paper aims to present possible convergences between Gramscian and Bourdieusian perspectives on the educational field, based on specific concepts. The concepts discussed include hegemony, symbolic violence, culture, and cultural capital. A theoretical reflection is conducted through bibliographic research, seeking to revisit the theorists’ writings and interpret them in a way that highlights aspects for considering the educational context. Finally, the possibility of analyses between these perspectives is examined by identifying relationships and articulations for education, based on the interrelation of Gramsci and Bourdieu’s concepts, even though the two authors have distinct theoretical orientations and points of divergence. Keywords: Antonio Gramsci. Pierre Bourdieu. Education.